Adaptations of Photosynthetic Electron Transport, Carbon Assimilation, and Carbon Partitioning in Transgenic Nicotiana plumbaginifolia Plants to Changes in Nitrate Reductase Activity. - Foyer, C. H. (1994)
Transgenic Nicotiana plumbaginifolia plants that express either a 5-fold increase or a 20-fold decrease in nitrate reductase (NR) activity were used to study the relationships between carbon and nitrogen metabolism in leaves. Under saturating irradiance the maximum rate of photosynthesis, per unit surface area, was decreased in the low NR expressors but was relatively unchanged in the high NR expressors compared with the wild-type controls. However, when photosynthesis was expressed on a chlorophyll (Chl) basis the low NR plants had comparable or even higher values than the wild-type plants. Surprisingly, the high NR expressors showed very similar rates of photosynthesis and respiration to the wild-type plants and contained identical amounts of leaf Chl, carbohydrate, and protein. These plants were provided with a saturating supply of nitrate plus a basal level of ammonium during all phases of growth. Under these conditions overexpression of NR had little impact on leaf metabolism and did not stimulate growth or biomass production. Large differences in photochemical quenching and nonphotochemical quenching components of Chl a fluorescence, as well as the ratio of variable to maximum fluorescence, (FV/FM), were apparent in the low NR expressors in comparison with the wild-type controls. Light intensity-dependent increases in nonphotochemical quenching and decreases in FV/FM were greatest in the low NR expressors, whereas photochemical quenching decreased uniformly with increasing irradiance in all plant types. Nonphotochemical quenching was increased at all except the lowest irradiances in the low NR expressors, allowing photosystem II to remain oxidized on its acceptor side. The relative contributions of photochemical and nonphotochemical quenching of Chl a fluorescence with changing irradiance were virtually identical in the high NR expressors and the wild-type controls. Zeaxanthin was present in all leaves at high irradiances; however, at high irradiance leaves from the low NR expressors contained considerably more zeaxanthin and less violaxanthin than wild-type controls or high NR expressors. The leaves of the low NR expressors contained less Chl, protein, and amino acids than controls but retained more carbohydrate (starch and sucrose) than the wild type or high NR expressors. Sucrose phosphate synthase activities were remarkably similar in all plant types regardless of the NR activity. In contrast phosphoenolpyruvate carboxylase activities were increased on a Chl or protein basis in the low NR expressors compared with the wild-type controls or high NR expressors. We conclude that large decreases in NR have profound repercussions for photosynthesis and carbon partitioning within the leaf but that increases in NR have negligible effects.